Search for displaced vertices arising from decays of new heavy particles in 7 TeV pp collisions at ATLAS - Aad, G.; Abat, E.; Abbott, B.; Abdallah, J.; Abdelalim, A. A.; Abdesselam, A.; Abdinov, O.; Abi, B.; Abolins, M.; Abramowicz, H.; Abreu, H.; Acerbi, E.; et al. (Elsevier BV, 2012)
We present the results of a search for new, heavy particles that decay at a significant distance from their production point into a final state containing charged hadrons in association with a high-momentum muon. The search is conducted in a pp-collision data sample with a center-of-mass energy of 7 TeV and an integrated luminosity of 33 pb^-1 collected in 2010 by the ATLAS detector operating at the Large Hadron Collider. Production of such particles is expected in various scenarios of physics beyond the standard model. We observe no signal and place limits on the production cross-section of supersymmetric particles in an R-parity-violating scenario as a function of the neutralino lifetime. Limits are presented for different squark and neutralino masses, enabling extension of the limits to a variety of other models.

8 pages plus author list (20 pages total), 8 figures, 1 table, final version to appear in Physics Letters B
Keywords: [PHYS.HEXP] Physics [physics]/High Energy Physics - Experiment [hep-ex]; particle: heavy; neutralino: lifetime; neutralino: mass; Atlas; CERN LHC Coll; sparticle; squark; FOS: Physical sciences; Atomic; Partícules (Física nuclear); High Energy Physics - Experiment; High Energy Physics - Experiment (hep-ex); Particle and Plasma Physics; [PHYS.HEXP]Physics [physics]/High Energy Physics - Experiment [hep-ex]; Nuclear; info:eu-repo/classification/ddc/530; Mathematical Physics; LHC; Atlas; High Energy Physics; hep-ex; ATLAS Detector; Atlas; LHC; pp collisions; [No Keywords]; Molecular; Física; Atlas; Nuclear & Particles Physics; Settore FIS/01 - FISICA SPERIMENTALE; Col·lisions (Física nuclear); Experimental High Energy Physics; Supersymmetry; HADRON-HADRON COLLISIONS; New particles; Particle Physics - Experiment; Astronomical and Space Sciences